SISTEM PENDUKUNG PERJALANAN WISATA DI KABUPATEN BANGKA BERBASIS ANDROID DENGAN ALGORITMA DIJKSTRA - Joshua Saputra; Bagus Mulyawan; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2018)
Application has been made as a system that help tourists who would plan their trip at Bangka Regency based on a shortest path. Furthermore, there also has a rent car feature with per day fare. Renter will be able to promote their cars for rent in the application so that the user can see all cars that have been rented by the renter. For the trip plan feature, system is using Dijkstra’s algorithm as a Support System to decide which path is the shortest one. The first current position and destination of tour places is determined by user. After choosing destination places, Dijkstra’s algorithm will find the shortest path gradually from each tour places that have been chosen by the user. And then the results are the minimum distances from each tour places. Most data of the locations in application are obtained using Google Maps API. However, some other data is saved in Server MySQL